Capturing Genomic Evolution of Lung Cancers through Liquid Biopsy for Circulating Tumor DNA. (14th March 2017) - Offin, Michael; Chabon, Jacob J.; Razavi, Pedram; Isbell, James M.; Rudin, Charles M.; Diehn, Maximilian; Li, Bob T.
Abstract : Genetic sequencing of malignancies has become increasingly important to uncover therapeutic targets and capture the tumor's dynamic changes to drug sensitivity and resistance through genomic evolution. In lung cancers, the current standard of tissue biopsy at the time of diagnosis and progression is not always feasible or practical and may underestimate intratumoral heterogeneity. Technological advances in genetic sequencing have enabled the use of circulating tumor DNA (ctDNA) analysis to obtain information on both targetable mutations and capturing real-time Darwinian evolution of tumor clones and drug resistance mechanisms under selective therapeutic pressure. The ability to analyze ctDNA from plasma, CSF, or urine enables a comprehensive view of cancers as systemic diseases and captures intratumoral heterogeneity. Here, we describe these recent advances in the setting of lung cancers and advocate for further research and the incorporation of ctDNA analysis in clinical trials of targeted therapies. By capturing genomic evolution in a noninvasive manner, liquid biopsy for ctDNA analysis could accelerate therapeutic discovery and deliver the next leap forward in precision medicine for patients with lung cancers and other solid tumors.